Numeracy Skills of Students in Solving Geometry Problems within the Bengkulu Context - Hartati, Puji; Muchlis, Effie Efrida; Susanta, Agus (Jurnal Pendidikan MIPA, 2024)
This study seeks to delineate the numeracy competencies of students in the geometry domain, framed by the cultural context of Bengkulu. Employing a qualitative descriptive approach, the research involved 35 students from Grade  XI. A of State High School 1 Bengkulu Tengah. The methodology included the use of open-ended numeracy tests specifically designed for geometry. Data analysis was conducted using descriptive statistics to delineate the spectrum of numeracy competency levels among the students. The findings showed that 4 students (13.33%) were at a low level of numeracy, 24 students (80.00%) at a medium level, and 2 students (6.67%) at a high level. Further analysis of students' numeracy skills across different geometric levels highlighted average proficiency scores of 81.66% in visualization, 66.67% in analysis, and a notably lower 40.00% in deduction. These results underscore the influence of culturally relevant numeracy problems on student performance. Consequently, these insights have significant implications for educational practices, particularly in the curation of instructional materials aimed at enhancing students' numeracy competencies.       Keywords: descriptive analysis, geometry domain, numeracy competency, cultural context of Bengkulu. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1518-1531